2018
DOI: 10.1186/s12885-018-4223-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness analysis of afatinib versus pemetrexed-cisplatin for first-line treatment of locally advanced or metastatic EGFR mutation positive non-small-cell lung cancer from the Singapore healthcare payer’s perspective

Abstract: BackgroundNon-small-cell lung cancer (NSCLC) accounts for 85% of all lung cancers and is associated with a poor prognosis. Afatinib is an irreversible ErbB family blocker recommended in clinical guidelines as a first-line treatment for NSCLC which harbours an epidermal growth factor receptor (EGFR) mutation. The objective of this study was to evaluate the cost-effectiveness of afatinib versus pemetrexed-cisplatin for first-line treatment of locally advanced or metastatic EGFR mutation positive NSCLC in Singapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
(49 reference statements)
1
23
0
Order By: Relevance
“…Most studies analyzed the cost-effectiveness of EGFR testing [25][26][27][28][29] or EGFR-TKI versus chemotherapy as first-line treatment [30][31][32][33][34]. Direct comparisons between different first-line EGFR-TKIs, however, have been performed less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies analyzed the cost-effectiveness of EGFR testing [25][26][27][28][29] or EGFR-TKI versus chemotherapy as first-line treatment [30][31][32][33][34]. Direct comparisons between different first-line EGFR-TKIs, however, have been performed less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previously accepted descriptors reported by Hong et al, 27 the publications were categorized as being of good reporting quality if they were scored 20-24, and were deemed to be of moderate and low reporting quality if they were scored 14-19.5 and <14, respectively. Only five studies were of good quality based on the CHEERS checklist score, while 18 were of moderate quality and two were of low quality. The quality rankings of these studies were not correlated in relation with the years of publication.…”
Section: Quality Of Reportingmentioning
confidence: 99%
“…Only two studies were based on decision trees without a Markov component 16,17 and four were adopted from the same partitioned survival model with three health states. [18][19][20][21] Another five studies [22][23][24][25][26] were found that reported no economic model.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations